SELEKSI PRIMER UNTUK ANALISIS KERAGAMAN GENETIK JENIS BITTI (Vitex coffassus) - . Gusmiaty; Muh. Restu; Ira Pongtuluran (PERENNIAL, 2012)
The successful of genomic DNA amplification using RAPD technique was determined by the sequence of primer’s base and primer compound in each reaction. The aim of research was finding the best primer for genetic diversity analyses of Bitti (Vitex coffassus). The results of amplification showed that number of band between one to five bands (110-600 bp). The primer of OPK-10, OPA-17, OPQ-07 and OPP-08 can be used for genetic diversity analyses of Bitti. The best primer used for genetic diversity analyses of Bitti was OPP-08 because it had the highest number of bands (5 bands). Key words: OPP-08, Primer Selection, Vitex coffassus